Asphaltene Removal – The Effect of Ionic Liquid to Asphaltene Characteristics - Siti Sarah binti Marjunit, Siti Sarah (Universiti Teknologi Petronas, 2009)
Crude oil composes of asphaltene, along with saturates, aromatics and resins (SARA) compound. Changes of temperature and pressure during oil production lead to the precipitation, flocculation and aggregation of asphaltene. This condition has caused many problems faced by the oil and gas industry, especially during production, refining, storage and transportation. This project aims to enhance existing method in removing asphaltene (through dispersion) using n-heptane solvent by replacing the solvent used for the process with the ionic liquid, IL solvent. The IL solvents used are [EMIM] toluene sulfonate and [BMIM] hydrogen sulfate. Experiment in treating crude oil and asphaltene with IL were conducted and mixing effect observed and analyzed by comparing weight percent, carbon, hydrogen and sulfur content, and also molecular weight of asphaltene before and after treatment. The experiments were carried out in two phases - first phase is to treat crude oil directly with the IL and the next phase is to extract asphaltene prior to treat with the IL. From the experiments that were conducted, ionic liquid used [BMIM]HSO4 shows potential in reducing asphaltene content. This interesting finding should be granted further analysis. In the other hand, [EMIM]tos is proven to increase the asphaltene weight percent, sulfur content and also molecular weight. This type of ionic liquid tends to cluster with asphaltene molecule, results in higher molecular weight compared to before treatment. If [EMIM]tos is going to be used in the industry, it is highly recommended to remove asphaltene that aggregates prior entering distillation column for fractionation.